Schamberg’s Disease - Psychosomatic Aspect and Homoeopathic Treatment (Homoeopathy for All, 2024)
Psychosomatic disorders are  Concerned with bodily symptoms  caused by emotional disturbances  i.e., relationships among social,  psychological, behavioral factors  on bodily processes and quality of  life. So complete cure from this can  be only achieved when the cause  for the generation of the mental  stress is identified. This review  highlights the important aspects  of the psychosomatic diseases  and the concept of homoeopathic  philosophy. According to  Homoeopathic philosophy, when an  individual becomes normalized by  the homoeopathic cure, the deeper  side of his being, the will and the  understanding or the rational mind  are balanced. With the change in  the mental and moral sphere, the  physical health improves with a high  degree of resistance to maladies of  all kinds. Such is the transition  from constitutional weakness and  suffering to homoeopathic health  and comfort.
Keywords: pigmentosa; chlordiazepoxide; schamberg